Kajian Pengembangan Model Ekonomi Sirkular (Circular Economy) Cabai sebagai Upaya Pengembangan Model Rantai Pasok Pertanian Berkelanjutan di Kabupaten Bogor - Sopyandi, Dede; Perdana, Tomy; Kusumawati, Riny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The loss of food and agricultural waste continues to pose challenges to sustainable agricultural development. The circular economy approach is believed to be able to address these challenges. However, the implementation of this approach requires the participation of all stakeholders in the supply chain, which must be coordinated through governance. Chili peppers are a high-value commodity that has the potential to generate income for farmers. This paper aims to understand how supply chain governance supports the implementation of a circular economy to minimize food loss and maximize the utilization of agricultural waste in chili pepper commodities. This study uses a mixed-method analysis, combining quantitative survey data and qualitative Focus Group Discussions (FGD). The chili pepper supply chain in Bogor Regency, West Java, Indonesia, is used as a case study. There are eight patterns in the chili pepper supply chain. The results show that 52.8% of food is lost along the traditional market-oriented chili pepper supply chain. In contrast, the food loss in the vegetable supply chain, which prioritizes modern markets (hotels and restaurants), is only 11%. This study finds that supply chain governance, including coordinated production planning, sales systems, price mechanisms, packaging systems, and low-quality product management, all contribute to reducing food loss based on circular economy principles. Regarding agricultural waste, the majority of chili pepper farmers (95%) do not manage their agricultural waste properly. Therefore, it is important to connect the supply and demand of agricultural waste and improve knowledge among farmers. This paper concludes that coordination and information exchange among supply chain actors are necessary to address the issues of food loss and agricultural waste.